Identification and characterization of the genetic changes responsible for the characteristic smooth‐to‐rough morphotype alterations of clinically persistent Mycobacterium abscessus. Issue 3 (17th September 2013) - Pawlik, Alexandre; Garnier, Guillaume; Orgeur, Mickael; Tong, Pin; Lohan, Amanda; Le Chevalier, Fabien; Sapriel, Guillaume; Roux, Anne‐Laure; Conlon, Kevin; Honoré, Nadine; Dillies, Marie‐Agnès; Ma, Laurence; et al.
Summary: Mycobacterium abscessus is an emerging pathogen that is increasingly recognized as a relevant cause of human lung infection in cystic fibrosis patients. This highly antibiotic‐resistant mycobacterium is an exception within the rapidly growing mycobacteria, which are mainly saprophytic and non‐pathogenic organisms. M. abscessus manifests as either a smooth (S) or a rough (R) colony morphotype, which is of clinical importance as R morphotypes are associated with more severe and persistent infections. To better understand the molecular mechanisms behind the S/R alterations, we analysed S and R variants of three isogenic M. abscessus  S/R pairs using an unbiased approach involving genome and transcriptome analyses, transcriptional fusions and integrating constructs. This revealed different small insertions, deletions (indels) or single nucleotide polymorphisms within the non‐ribosomal peptide synthase gene cluster mps1‐mps2‐gap or mmpl4b in the three R variants, consistent with the transcriptional differences identified within this genomic locus that is implicated in the synthesis and transport of Glyco‐Peptido‐Lipids (GPL). In contrast to previous reports, the identification of clearly defined genetic lesions responsible for the loss of GPL‐production or transport makes a frequent switching back‐and‐forth between smooth and rough morphologies in M. abscessus highly unlikely, which is important for our understanding of persistent M. abscessus infections.